2020
DOI: 10.3390/cells9020320
|View full text |Cite
|
Sign up to set email alerts
|

Tumors Provoke Inflammation and Perineural Microlesions at Adjacent Peripheral Nerves

Abstract: Cancer-induced pain occurs frequently in patients when tumors or their metastases grow in the proximity of nerves. Although this cancer-induced pain states poses an important therapeutical problem, the underlying pathomechanisms are not understood. Here, we implanted adenocarcinoma, fibrosarcoma and melanoma tumor cells in proximity of the sciatic nerve. All three tumor types caused mechanical hypersensitivity, thermal hyposensitivity and neuronal damage. Surprisingly the onset of the hypersensitivity was inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The claudin-1 antibody was raised against a synthetic peptide within human claudin-1 aa 150 to the C-terminus. The ab15098 antibody was used for targeting peripheral nerve perineurium ( Cohnen et al, 2020 ), as well as for applications of IHC of many other paraffin-embedded tissues [e.g., skin ( Kim et al, 2016 ), intestine ( Gumber et al, 2014 ; Mandle et al, 2019 ), and kidney ( Koda et al, 2014 )]; other claudin-1 antibodies were also used to label perineurium in peripheral nerves ( Pummi et al, 2004 ; Rittner et al, 2012 ; Piña et al, 2015 ; Reinhold et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The claudin-1 antibody was raised against a synthetic peptide within human claudin-1 aa 150 to the C-terminus. The ab15098 antibody was used for targeting peripheral nerve perineurium ( Cohnen et al, 2020 ), as well as for applications of IHC of many other paraffin-embedded tissues [e.g., skin ( Kim et al, 2016 ), intestine ( Gumber et al, 2014 ; Mandle et al, 2019 ), and kidney ( Koda et al, 2014 )]; other claudin-1 antibodies were also used to label perineurium in peripheral nerves ( Pummi et al, 2004 ; Rittner et al, 2012 ; Piña et al, 2015 ; Reinhold et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dysfunction and breakage of the blood–spinal cord barrier is observed in several neurodegenerative disorders, peripheral neural injury-induced inflammatory pain, and chemotherapy-induced neuropathic pain [ 26 , 27 ]. In a rat sciatic nerve model, recruitment of inflammatory materials outside the nerve led to damage of the epineurium and depletion of epineural adipocytes [ 21 , 28 ]. Simultaneously, pro-nociceptive and pro-inflammatory mediators can enter the sciatic nerve through microlesions caused by neural damage [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat sciatic nerve model, recruitment of inflammatory materials outside the nerve led to damage of the epineurium and depletion of epineural adipocytes [ 21 , 28 ]. Simultaneously, pro-nociceptive and pro-inflammatory mediators can enter the sciatic nerve through microlesions caused by neural damage [ 28 ]. Therefore, non-myelinating Schwann cells may no longer protect non-myelinated neurons, causing tactile allodynia and loss of function of thermal sensitivity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further lipidomic approach indicated the damage of neuronal myelin sheaths, decreased energy metabolism and the loss of epineural adipocytes which have an important protective role in peripheral nerves. The authors concluded that inhibition of inflammatory processes at the sciatic nerve or preserving peri- and epineural integrity might constitute suitable approaches to decrease tumor-induced pain [ 8 ].…”
mentioning
confidence: 99%